Síntese, caracterização e estudos cinéticos da isomerização de compostos de Ru(II) contendo ligantes (X-bipy) ( X=-H, -NO2, -Me, - COOH, -SMe, O=SMe, -Cl, -OMe) - Santiago, Marcelo Oliveira (Universidade Federal de São Carlos, 2004)
The synthesis of coordination compounds containing bipyridine derivative ligands and the influence of the substituent groups on the physical and chemical properties were studied in this work. Mixed compounds of the type [RuCl2(P P)(X bipy)] were synthesized, where X - bipy represents the bipyridine derivatives and P - P = triphenylphosphine (PPh3)2, 1,4-bis(diphenilphosphino)butane (dppb). The characterization of the compounds showed that the isomer formed in solution is dependent on the phosphine used. The isomer of the compounds containing the triphenylphosphine exhibited a structure where the phosphine groups are mutually in trans position. For the biphosphine compounds, dppb is trans to N-heterocyclic ligand. The spectroscopic and electrochemical properties of the compounds showed dependence with substituent group of the bipyridine. It was observed a linear correlation of the pKa values of the X-bipy ligands with the redox potential of the complexes. The decrease of the pKa value with the increase in the electronwithdrawing ability of the X groups makes the ligand less basic. This effect enhances the π-backbonding interactions, which implies in the energy decrease of the MLCT transitions and in the redox potential increase of the metal center. For the [RuCl2(dppb)(X-bipy)] complexes, the isomerization reactions under light incidence were monitored by electronic spectroscopy or differential pulse voltammetry. The photolysis study of the compound with the 2,2'-bipyridine ligand allowed the assignment of the field ligand state for its photochemical activity. The kinetic data supplied the assignment of a twist mechanism for the isomerization process. It was observed an increase in the rate constant value for this process with the increase pka values of the ligand. The reactivity of the compound [RuCl2(COD)]n, COD is 1,5- cyclooctadiene ligand, with the substituted bipyridine was studied in order to obtain compounds containing different compositions with changes in reaction conditions. Compounds of the type [RuCl2(COD)(X-bipy)], for X = H and Me, were obtained and characterized by microanalysis, hydrogen nuclear magnetic resonance (RMN) and electrochemical techniques. The reactions with other bipyiridines resulted in mixtures of compounds of hard purification, needing a more systematic studies for the correct attribution of their composition and structures. Tris(diimine)ruthenium complexes, [Ru(X-bipy)3](PF6)2 with X = H, Me, MeO, MeS, were obtained and characterized by microanalysis, hydrogen nuclear magnetic resonance and electrochemical techniques. With substituent groups containing sulfur atom, MeS and MeSO, polinuclear complexes were obtained. The [RuCl2(P-P)(MeS-bipy)][(µ)-RuCl2(P-P)], [RuCl2(CO)(PPh3)2]2[(µ) RuCl2(dppb)(MeS-bipy)] and {[RuCl2(dppb)]3[(µ)-Ru(MeSObipy) 3]}(PF6)2 compounds were synthesized and characterized by spectroscopic and electrochemical techniques. An interesting electronic conducting mechanism was observed. The sulfur atom is believed to withdraw electron density of the metallic center by backdonation interaction transferring to the pyridine ring which, by being more basic, transfer part of this density to the second metallic center.
Sinthesis, characterization and isomerization kinetic study of Ru(II) compounds containing X-bipy (X= −H, −NO2, Me−, −COOH, −SMe, O = SMe, −Cl, −OMe) ligands
Keywords: Complexos metálicos; Rutenio; Fosfina; Bipiridinas substituidas; Fotoisomerização; Compostos de coordenação; CIENCIAS EXATAS E DA TERRA::QUIMICA